Ratification of the UN Anti-Corruption Convention: Legal and Political Implications in Indonesia and its Context within Southeast Asian International Law Discourse - Nuraini, Apriliana Rahma; Niel, Edward (Faculty of Law, Universitas Negeri Semarang, 2024)
This paper scrutinizes Indonesia's ratification of the UN Anti-Corruption Convention, examining its legal and political implications within Southeast Asia's international law discourse. Analyzing treaty provisions alongside Indonesia's legal framework, it assesses challenges and opportunities in combating corruption. The study emphasizes several key findings. Firstly, domestically, ratification showcases Indonesia's commitment to combat corruption, addressing a long-standing governance and economic development issue. Aligning with international standards signals intent to fortify anti-corruption efforts, bolster transparency, and augment accountability mechanisms. This aligns with fostering good governance practices vital for sustainable development and attracting foreign investment. Secondly, ratification holds political significance, affirming the government's dedication to tackling corruption, potentially enhancing its legitimacy. However, effective implementation may face hurdles due to entrenched political interests and bureaucratic challenges. In the Southeast Asian context, Indonesia's ratification serves as a model for regional cooperation against corruption. As a major economy and populous nation, Indonesia's commitment sets a precedent for collective action. It underscores the importance of regional collaboration in combating corruption, opening avenues for dialogue, collaboration, and capacity-building initiatives. This offers prospects for strengthening anti-corruption frameworks and mechanisms both nationally and regionally. In conclusion, Indonesia's ratification of the UN Anti-Corruption Convention signifies a pivotal step in combating corruption domestically and regionally. While it showcases political will and potential for regional cooperation, effective implementation remains contingent on overcoming internal challenges and fostering collaboration across Southeast Asia. This study illuminates the complex interplay between national and international efforts to combat corruption, contributing to a deeper understanding of the regional dynamics at play.